Mechanistic Insights for Dry Reforming of Methane on Cu/Ni Bimetallic Catalysts: DFT-Assisted Microkinetic Analysis for Coke Resistance - Ahmed Omran (9269789) (2020)
Density functional theory (DFT) calculations have been utilized to evaluate the complete reaction mechanism of methane dry reforming (DRM) over Ni2Cu (111) bimetallic catalyst. The detailed catalytic cycle on Ni2Cu (111) catalyst demonstrated superior coke resistance compared to pure Ni (111) and Ni2Fe (111) reported in the literature. Doping Cu in the Ni–Ni network enhanced the competitive CH oxidation by both atomic O and OH species with the latter having only 0.02 eV higher than the 1.06 eV energy barrier required for CH oxidation by atomic O. Among the C/CH oxidation pathways, C* + O* → CO (g) was the most favorable with an energy barrier of 0.72 eV. This was almost half of the energy barrier required for the rate-limiting step of CH decomposition (1.40 eV) and indicated enhanced coke deposition removal. Finally, we investigated the effect of temperature (800~1000 K) on the carbon deposition and elimination mechanism over Ni2Cu (111) catalyst. Under those realistic DRM conditions, the calculations showed a periodic cycle of simultaneous carbon deposition and elimination resulting in improved catalyst stability. Other Information Published in: Catalysts License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/catal10091043 Additional institutions affiliated with: Chemical Engineering Program - TAMUQ